Optimization of Humanist Law Enforcement in Order to Realize the Paradigm of Civilian Police - Setiadi Setiadi (Unnes Law Journal, 2023)
The world's development today requires the Indonesian National Police (INP), must be able to adapted the community's needs and demands. Indonesian Council Decree Number VI / MPR-RI / 2000 arrange the INP as a civilian institution and separate from the Indonesian military, thus requiring INP to change the identity to become a security officer with a civilian character. Building the organizational paradigm of INP to become civilian and democratic police is very necessary, so the role and function of INP as a protector and public servant can be achieved. Humanist law enforcement without using violents will build INP faces became more calm and protective. How is the humanist law enforcement towards the realization of the civilian police paradigm? Humanist law enforcement by the Cilacap Police has not been optimal, it can be seen in the regulations regarding humanist law enforcement within the Police organization that have not been realized, the competence of police officers is not yet optimal in the knowledge, attitudes, and practices, regarding the humanist and the Civil Police paradigm, infrastructure has not been fully supported, community law awareness is still low, and legal culture has not yet been implemented in society. This is influenced by developments in the strategic environment as well as internal and external factors. The SWOT analysis followed by the Anallytical Hierarchy Process (AHP) to produces IFAS, EFAS, and SFAS to determine the action plan of the strategy. The implementation of short-, medium- and long-term strategies obtained from AHP calculations is expected to realize the expected ideal conditions. The implementation of programs in the strategy that has been set is expected to optimize humanism law enforcement to realize the Civilian Police paradigm.